The Legal Vacuum in Law Enforcement of Digital Currency Crimes by the Police - Sapta Eka Yanto; Faisal Santiago (Riviera Publishing, 2024)
The rapid development of digital currencies has introduced significant legal challenges, particularly concerning currency counterfeiting crimes. Existing regulations in Indonesia are often considered inadequate to address the complexities of such offenses, creating a substantial legal vacuum. This study employs a normative juridical research method with legislative and conceptual approaches to examine legal provisions and analyze the characteristics of digital currencies within the legal framework. The findings reveal critical regulatory gaps in defining and penalizing digital currency-related crimes, highlighting the urgent need for legal reforms. Key recommendations include strengthening regulatory frameworks, enhancing police investigative capabilities, and fostering cooperation between law enforcement and financial institutions. Establishing more precise legal definitions and providing specialized training for police officers are essential steps toward building a more responsive and effective law enforcement system capable of addressing digital-era crimes. These measures aim to improve legal enforcement practices and support the development of comprehensive digital currency regulations.